2007
DOI: 10.1111/j.1365-2885.2007.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of imidocarb dipropionate in swine

Abstract: A two-way crossover study was performed in eight healthy young pigs to determine the pharmacokinetics of imidocarb dipropionate (IMDP) following intravenous (2 mg/kg b.w.) and intramuscular (2 mg/kg b.w.) administrations. Each animal received one intravenous and one intramuscular injection with a 30-day washout period between the two-treatments. Plasma concentrations were measured by high-performance liquid chromatography (HPLC) assay with UV detector at regular intervals for up to 24 h post-injection. Intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the test group, IMD was quickly absorbed and detected in all treated animals in 10 min after administration. A plateau of the concentration was 2257.5±273.62 ng/mL in 2.14±0.67 h. It was eliminated very slowly with T 1/2 31.77±25.75 h, which is much longer than elimination in swine (T 1/2 13.91±2.73 h) [1], dogs (T 1/2 3.45±0.75 h) and goats (T 1/2 4.18±1.57 h, 7.73±1.73 h) [32], horses (5.14±2.84 h) [31] and white-tailed deer (7.73±1.73 h) [7]. This may be due to the differences in animal species and administration routes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the test group, IMD was quickly absorbed and detected in all treated animals in 10 min after administration. A plateau of the concentration was 2257.5±273.62 ng/mL in 2.14±0.67 h. It was eliminated very slowly with T 1/2 31.77±25.75 h, which is much longer than elimination in swine (T 1/2 13.91±2.73 h) [1], dogs (T 1/2 3.45±0.75 h) and goats (T 1/2 4.18±1.57 h, 7.73±1.73 h) [32], horses (5.14±2.84 h) [31] and white-tailed deer (7.73±1.73 h) [7]. This may be due to the differences in animal species and administration routes.…”
Section: Discussionmentioning
confidence: 90%
“…Eperythrozoon is a genus of common bacteria, formerly classified in the Rickettsiaceae that can cause infectious anthropozoonosis [1,2]. Thousands of cattle are infected with eperythrozoonosis annually and severe infections often result in mortality.…”
Section: Introductionmentioning
confidence: 99%
“…IM has the resistance to biotransformation processes; the form remaining in animal organisms is almost the original drug (Crescenzo et al, 2002). Therefore, overdose and incorrect use may cause IM accumulation in organs, principally liver and kidney, followed by heart, muscle and brain tissues, and had potential neurotoxicity (Aliu et al, 1977;Lai et al, 2002;Su et al, 2007). Studies shown that IM have been found in milk and animal tissues, which leads to food safety issues and threaten human health (Belloli et al, 2006;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine, it is used in cattle, horses, sheep, and domestic animals including cats and dogs, for the treatment of anaplasmosis and babesiosis (4)(5)(6)(7)(8). Findings of recent studies show that significant residues of imidocarb were detected in bovine and ovine tissues and milk following the administration of 14 C-imidocarb dipropionate (2,3,9). For this reason, maximum residue limits (MRL) of imidocarb have been set by CODEX, Europe, Middle East and Africa and other countries, including Japan and Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Imidocarb is usually administered as dipropionate salt (1)(2)(3). In veterinary medicine, it is used in cattle, horses, sheep, and domestic animals including cats and dogs, for the treatment of anaplasmosis and babesiosis (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%